Diagnostic and Surgical Challenges in Recurrent Dermatofibrosarcoma Protuberans: A Case Report - Yogesh Manek; Swati Deshpande; Darshana Tote; Suhas Jajoo; Bhagyesh Sapkale (Journal of Clinical and Diagnostic Research)
Dermatofibrosarcoma Protuberans (DFSP) is a low-grade cutaneous soft-tissue sarcoma that originates in the dermis and infiltrates deeper structures. It comprises less than one percent of all soft-tissue sarcomas and is histologically defined by their slow growth, localised invasiveness and a tendency to recur when not adequately excised. However, unlike other cancers, distant metastasis is relatively uncommon; the invasive nature of DFSP infiltration causes diagnostic and therapeutic challenges. DFSP can involve any area of the body; however, it predominantly favours the trunk and extremities. The mainstay of management is wide local excision, which should achieve negative margins, as inadequate margins have a propensity to recur. Recurrent cases require specific surgical management to balance oncological security with the management of their consequences. The presented case involves a 72-year-old man with recurrent DFSP, manifesting as a long-standing swelling of the left great toe that progressively increased over 10 years. Initially, conservative treatment was attempted, but the condition became symptomatic, leading to excision and a diagnosis of Chronic Granulomatous Changes (CGC) and liquefactive necrosis. Although the swelling was initially excised, it recurred after eight months and was treated by amputation due to its aggressive nature and the impossibility of definitive resection. Radical surgical re-intervention for wound dehiscence, which later reopened, was supplemented by Split-thickness Skin Grafting (SSG). In the management of recurrent soft-tissue tumours, early diagnosis and individualised treatment planning should be emphasised to maximise patient outcomes and minimise recurrence.